Public Debt Sustainability Under Uncertainty : An Invariant Set Approach - Rozenov, Rossen (IMF Working Papers; Working Paper, 2017)
The paper offers an approach to assessing the sustainability of public debt taking into account the effect of fiscal policy on output, as well as uncertainty in the model parameters and system dynamics. Uncertainty is specified in general terms, and the analysis is based on the notion of invariant sets. Examples are provided to illustrate how the method can be applied in practice.